曾国藩《十八家诗钞》研究 = A study of Zeng Guofan's anthology of eighteen poets - 钱昊 Qian, Hao (Nanyang Technological University, 2017)
《十八家诗钞》是清人曾国藩（1811-1872）编纂的一部诗歌选本，选取自魏至金十八位诗人之五七言古近体诗歌 6599 首，勾勒了中国五七言诗歌的 演进史。本文从四个角度对《十八家诗钞》展开论述。 第一章论述《十八家诗钞》的选钞方式与选诗旨趣。曾国藩对魏晋南北 朝诗、唐诗、宋诗及元好问诗的选钞运用了不同的选钞方式，遴选了不同种类的诗歌，体现了曾氏对各体诗歌在不同时代创作成就的体认，表现出对时代诗风的熟稔。《十八家诗钞》的选诗旨趣主要有以下四个方面：兼收并蓄、重点突出；梳理脉络、勾勒诗史；理性务实、兼采唐宋；注重审美、陶冶意趣。 第二章论述《十八家诗钞》的校注特征。曾国藩读书治学重视考据、训诂，在《十八家诗钞》中，字句的详解或能揭示典故，或能反映创作主体的身份与性情，抑或能比对不同版本的诗集，对字句予以商榷和纠谬。《十八家诗钞》在校注杜诗诗时征引了曾被清政府下令禁毁的《钱注杜诗》，从知人论世、评价诗艺两方面援引大量《钱注杜诗》的内容，此举体现出晚清文网松弛与汉族士大夫之崛起。除《钱注杜诗》外，《十八家诗钞》亦征引了大量前代著作用于校注，针对不同诗人诗作，曾国藩征引的著作不同，于经、史、子、集四部各有侧重，体现了其深厚的学养。 第三章论述桐城诗学视域下的《十八家诗钞》。曾国藩被视为“桐城中兴明主”，本章以桐城诗学的发展脉络为线索，论述曾国藩对桐城派诗论的继承，探讨其在桐城诗学“浅弱不振”之际“出而振之”的功绩，并以《十 八家诗钞》的选诗实践加以说明，最后分析曾氏诗论及《十八家诗钞》对曾门弟子和晚期桐城学人的诗论与诗选的影响。 第四章论述《十八家诗钞》与清代的诗选与诗评。清代诗选与诗评数量繁多，本章将《十八集诗钞》置入清代诗论史的脉络当中，结合清代汉魏六朝诗及唐宋诗两大类选本的发展流变考察《十八家诗钞》，并分别从两类选本中摘取王闿运《八代诗选》与《御选唐宋诗醇》与《十八家诗钞》作对比研究，最后总论《十八家诗钞》在清代诗选与诗评中的价值与地位。 Anthology of Eighteen Poets (Shibajia Shichao 十八家诗钞) was compiled by Zeng Guofan (1811-1872), a famous politician and litterateur in Qing Dynasty. This anthology included 6599 traditional Chinese poems wrote by eighteen poets from Wei Dynasty (220-266) to Jin Dynasty (1115-1234). These poems varied in their forms from five-character lines to seven-character lines poems, from archaic to rhymed styles. This collection reflected the development of Chinese five-character and seven-character poems. This thesis aims at a comprehensive research on Anthology of Eighteen poets, including four chapters as below. Chapter 1：The methods and purports applied in compiling Anthology of Eighteen poets. Zeng Guofan used different methods in selecting poems of different periods: Wei, Jin, Southern and Northern Dynasties, Tang Dynasty, Song Dynasty and Jin Dynasty (represented by Yuan Haowen). The purports of Anthology of Eighteen poets can be illustrated in four aspects, namely: making an all-embracing selection but also with emphases on certain types; Outlining the history of poetry; adopting both Tang-Style and Song-Style poems; Cultivating aesthetic tastes. Chapter 2: The annotations of Anthology of Eighteen poets. Zeng Guofan had a good command in textology and exegesis. In Anthology of Eighteen poets, Zeng Guofan’s annotations on words and sentences figured out both historical allusions and the poets’ characteristics. What is more, Zeng Guofan compared different editions of anthologies and corrected some of the words and sentences. In the annotations to Du Fu’s poems, Zeng Guofan quoted Qian Qianyi’s Annotation of Du Fu’s poetry (Qian Zhu DuShi 钱注杜诗) which was once banned by the government in Qing Dynasty. It indicates the looser cultural environment in Late-Qing Dynasty and the rise of Han literati. Along with Qian Qianyi’s Annotation of Du Fu’s poems, Zeng Guofan quoted many works in ancient China. He cited various works in order to deal with different poems, including Confucian Classics, historical works, philosophical works, and literary works. This also reflected Zeng Guofan’s profound knowledge. Chapter 3: Anthology of Eighteen poets through the perspective of Tongcheng桐城 poetics. Zeng Guofan was reputed as the key person in the resurgence of Tong Cheng Poem School. This chapter analyzes Anthology of Eighteen poets in the the background of Tongcheng poetics developmental path, discussing Zeng Guofan’s inheritance in poetics of the early Tongcheng School, his contribution to the resurgence of Tongcheng poetics, and his influences to his student and literati of the late Tongcheng School. Chapter 4: Anthology of Eighteen poets and other poetic commentaries and anthologies in Qing Dynasty. Poetic commentaries and anthologies flourished in Qing Dynasty. In this chapter, Anthology of Eighteen poets is analyzed according to the poetic history of Qing Dynasty and compared to anthologies of Han, Wei, Six Dynasties, Tang, and Song Dynasties. Further on, Anthology of Eighteen poets has been compared thoroughly with Wang Kaiyun’s Anthology of Eight Dynasties (Badai Shixuan 八代诗选) and Imperial Anthology of poems of Tang and Song（Yuxuan Tangsong Shichun御选唐宋诗醇）. In the conclusion, the value and historical status of Anthology of Eighteen poets in Qing Dynasty has been discussed.